Penerapan Media E-Booklet dalam Pembelajaran Ikatan Kimia di SMA - Lingga, Aknes Dianti; Pasar Maulim Silitonga (ARKA INSTITUTE, 2022)
This study aims to measure students' learning outcomes in class X SMA PAB 8 Saentis Percut Sei Tuan, taught between E-booklets and PPT media. The samples in this study were taken by random sampling technique by lottery. The type of research used is a quasi-experimental design (Quasi-Experimental Design. The data collection technique begins with the preparation stage and the implementation stage. As a prerequisite for hypothesis testing, the sample group data is tested for normality and homogeneity. Then hypothesis testing is carried out with SPSS Statistics 20 with criteria for a significant level of 5 %. Based on the results of data processing student learning outcomes, the average value of student learning outcomes in experimental class 1 using e-booklet media in the learning process is higher. Then the average value of student chemistry learning outcomes in practical class 2 using PPT media is reinforced in the second hypothesis test; the sig (2-tailed) score on SPSS is 0.015. This study also shows that the average value of student learning outcomes who are taught by the application of E-booklet media is higher than the KKM. This is reinforced by the first hypothesis test where the result of the sig (2-tailed) value of 0.000 using the one-sample t-test analysis on SPSS. According to the third hypothesis test, a significant value of 0.000 < 0.05 obtained in 84% of students taught by e-booklet media reached the KKM.